Comparison of Corticotrophin and Prednisolone in Treatment of Idiopathic Facial Paralysis (Bell's Palsy). Issue 5778 (2nd October 1971) - Taverner, D.; Cohen, S. B.; Hutchinson, B. C.
Abstract : In a controlled trial of the effects of intramuscular corticotrophin and oral prednisolone in the treatment of acute Bell's palsy 186 successive patients with idiopathic facial palsy were grouped for age and duration of palsy. They were then allocated at random to either corticotrophin or prednisolone therapy in pairs. The results were: (1) 94 received corticotrophin and 32 developed some degree of denervation and 92 received prednisolone and 13 developed some degree of denervation (P <0·005); (2) six of the corticotrophin group became severely denervated (less than 50% recovery) compared with none of the prednisolone group (P <0·02); (3) the best results were obtained in the younger patients (less than 45 years old) treated on the first or second day of palsy; and (4) side effects were minimal. It is concluded that oral prednisolone is the treatment of choice for idiopathic facial (Bell's) palsy.